Gradient estimates for problems with Orlicz growth. (May 2020) - Chlebicka, Iwona
Abstract: We study a general nonlinear elliptic equation in the Orlicz setting with data not belonging to the dual of the energy space. We provide several Lorentz-type and Morrey-type estimates for the gradients of solutions under various conditions on the data.